1992
DOI: 10.1073/pnas.89.5.1695
|View full text |Cite
|
Sign up to set email alerts
|

Highly conserved repetitive DNA sequences are present at human centromeres.

Abstract: Highly conserved repetitive DNA sequence clones, largely consisting of (GGAAT HeLa-ceil nuclear proteins recognize this sequence with a relative affinity >105. The extreme evolutionary conservation ofthis DNA sequence, its centromeric location, its unusual hydrogen bonding properties, its high affinity for specific nuclear proteins, and its similarity to functional centromeres isolated from yeast suggest that this sequence may be a component of the functional human centromere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
136
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(142 citation statements)
references
References 29 publications
6
136
0
Order By: Relevance
“…These sequences are known to bind specific proteins which initiate the formation of a multiprotein complex (kinetochore) that binds to the ends of microtubules and helps in chromosomal migration during cell division [1]. Grady et al [2] have observed some proteins that bind specifically to the human centromeric repeat that we have studied. The dynamic base pairing scheme proposed above may play an important role in the specific protein recognition of this DNA repeat.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…These sequences are known to bind specific proteins which initiate the formation of a multiprotein complex (kinetochore) that binds to the ends of microtubules and helps in chromosomal migration during cell division [1]. Grady et al [2] have observed some proteins that bind specifically to the human centromeric repeat that we have studied. The dynamic base pairing scheme proposed above may play an important role in the specific protein recognition of this DNA repeat.…”
Section: Resultsmentioning
confidence: 97%
“…This repeat is also found on chromosomes that show high incidence of nondysjunction and other mitotic/meiotic abnormalities [3]. Grady et al [2] have shown recently that the purine strand of this sequence, (AATGN)n , forms a stable structure which likely incoporates G-A mismatched base pairs. In addition, this sequence behaved anomalously in gel electrophoresis.…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of single-stranded DNA at heterochromatin blocks could originate from their characteristic enrichment on highly repetitive satellite DNA sequences, which is likely to promote strand slippage events during DNA replication. In this respect, the dodeca-satellite, like general satellites showing Pu-Py strand asymmetry, appear especially suited for the binding of DDP1 or vigilins in general, since its two strands show drastically different structural properties (6,7,13,14,27). The pyrimidine-rich strand could remain unstructured, providing long single-stranded DNA stretches, as required for efficient DDP1 binding.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro, the dodeca-satellite can form altered DNA structures in which the G strand forms very stable intramolecular hairpins while the complementary C strand remains unstructured (13). Other centromeric satellites, such as the abundant Drosophila AAGAG satellite, show similar structural properties (6,7,14,27). Formation of these altered DNA structures could therefore provide an adequate substrate for the efficient binding of DDP1 to heterochromatin.…”
mentioning
confidence: 99%